A scholarship program for academic staff to develop exemplary online learning tasks - Herrington, Anthony; Schrape, Judy; Flintoff, Kim; Leaver, Tama; Molineux, Matthew; O'Hare, Sheena (ascilite, 2010)
There is a strong impetus for blended learning approaches to be more widely adopted in higher education but finding an effective model for professional development of teaching staff can be problematic. In 2009, Curtin University developed an eTeaching and Learning Scholarship program for academic staff to develop exemplary online learning tasks that could be shared with the university community and inform future online teaching within their disciplines. This paper describes the design of the professional learning program together with early encouraging results that indicate both the willingness of the eScholars to incorporate additional learning technologies to extend the affordances of the university provisioned systems and to embrace authentic learner-centred tasks.